(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
Since the 2009 launch of NT Live, the National Theatre has been at the forefront of UK livecasting so the calls to respond to the complete lockdown of the UK in March 2020 weren’t surprising. This paper will analyse how this pandemic response utilised the multiple temporalities of NT Live to create a theatrical event in viewers’ homes. Despite using past recordings, the NT At Home programme was a response to a specific historical event and was structured around an “ontological now” that in return shaped the reception of those recordings. NT Live capitalised on the liveness and the exclusivity of their broadcasts. Performances were shown at a set time, streamed simultaneously into cinemas. NT At Home challenged every part of this system of liveness and in doing so created its own contradictory and fluid temporal identity. In this paper I will draw on liveness studies from multiple disciplines to cover three aspects of these new temporalities and present a case study of liveness practice. NT Live capitalised on the liveness and the exclusivity of their broadcasts. Performances were shown at a set time, streamed simultaneously into cinemas. NT At Home challenged every part of this system of liveness and in doing so created its own contradictory and fluid temporal identity. In this paper I will draw on liveness studies from multiple disciplines to cover three aspects of these new temporalities and present a case study of liveness practice.